Human Papillomavirus–Associated Oropharyngeal Cancer: Patterns of Nodal Disease. (2nd October 2018) - Plonowska, Karolina A.; Strohl, Madeleine P.; Wang, Steven J.; Ha, Patrick K.; George, Jonathan R.; Heaton, Chase M.; El‐Sayed, Ivan H.; Mallen‐St. Clair, Jon; Ryan, William R.
Abstract : Objective: To characterize patterns of neck lymph node (LN) metastases in human papillomavirus (HPV)–associated oropharyngeal squamous cell carcinoma, represented by p16 positivity (p16+OPSCC). Study Design: Case series with chart review. Setting: Tertiary care center. Subjects and Methods: Neck dissection (ND) specimens of nonirradiated p16+OPSCC patients were analyzed for frequencies of clinically evident and occult LNs by neck level. Local, regional, and distant recurrences were reviewed. Results: Seventy p16+OPSCC patients underwent primary site transoral robotic surgery and 82 NDs of varying levels. Metastatic pathologic LNs were found at the following frequencies: 0% (0/28) in level I, 75.6% (62/82) in level II with 57.4% (35/61) in level IIA and 13.1% (8/61) in level IIB, 22.0% (18/82) in level III, 7.0% (5/71) in level IV, and 6.3% (1/16) in level V. The level V LN was clinically evident preoperatively. Five of 21 (23.8%) elective NDs contained occult LNs, all of which were in level II and without extranodal extension. Twenty‐seven (38.6%) patients underwent adjuvant radiation; 19 (27.1%) patients underwent adjuvant chemoradiation. With a mean follow‐up of 29 months, 3 patients had developed recurrences, with all but 1 patient still alive. All patients who recurred had refused at least a component of indicated adjuvant treatment. Conclusions: For p16+OPSCC, therapeutic NDs should encompass any levels bearing suspicious LNs and levels IIA‐B, III, and IV, while elective NDs should be performed and encompass at least levels IIA‐B and III. These selective ND plans, followed by indicated adjuvant treatment, are associated with a low nodal recurrence rate.